1999
DOI: 10.1051/gse:19990104
|View full text |Cite
|
Sign up to set email alerts
|

Selection for reduced muscle glycolytic potential in Large White pigs. II. Correlated responses in meat quality and muscle compositional traits

Abstract: -A selection experiment was conducted over six generations in a purebred French Large White population presumably free of the HAL" and RN-alleles. Two lines were taken from the same base population and were contemporarily bred: one control line (C) and one line (S) (-0, 42 ! 0, 12

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
1
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 6 publications
2
8
1
2
Order By: Relevance
“…Similar variations were also reported in pigs by Larzul et al [16], with heritabilities close to zero for the colour parameters measured in a predominantly red muscle and moderate ones for the same parameters in intermediate or predominantly white muscles. It is possible that the low heritabilities we obtained for the quality indicators in the thigh reflected a higher impact of the environmental factors or alternatively, were simply related to the difficulty of measuring meat quality on a heterogeneous muscle such as the IT muscle.…”
Section: Discussionsupporting
confidence: 88%
“…Similar variations were also reported in pigs by Larzul et al [16], with heritabilities close to zero for the colour parameters measured in a predominantly red muscle and moderate ones for the same parameters in intermediate or predominantly white muscles. It is possible that the low heritabilities we obtained for the quality indicators in the thigh reflected a higher impact of the environmental factors or alternatively, were simply related to the difficulty of measuring meat quality on a heterogeneous muscle such as the IT muscle.…”
Section: Discussionsupporting
confidence: 88%
“…Nevertheless, these results diverged from those reported in broilers (Le Bihan-Duval et al, 2001), in which initial and ultimate meat pH measures were not genetically associated. Genetic correlation estimates near zero among these traits are reported in pigs (Larzul et al, 1999), which could be attributed to independent control mechanisms for initial and ultimate pH. This possibility was not verified by the current study, in which a decrease in pH i seemed to be able to induce to a decrease in pH u , suggesting that the same genes could be involved with the control of both traits.…”
Section: Resultscontrasting
confidence: 52%
“…Similarly, Larzul et al (1997Larzul et al ( , 1999 also found a genetic correlation between glycogen and pH. In addition, Le Roy et al (1998) found a reduction of approximately 13 mmoles/g of glycogen when pigs were selected for lower longissimus dorsi (in vivo) glycolytic potential for six generations.…”
Section: Discussionmentioning
confidence: 91%